Efektivitas Sistem Informasi Manajemen Pemasaran Dalam Penerapan CRM Untuk Meningkatkan Loyalitas Pelanggan Pada Perusahaan Ritel - Fenny Purwani; Dzurriya Alkarimah; Lilis Anderwani; Mesi Kurniawan; Irmalia, Irmalia (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This article discusses the effectiveness of Marketing Management Information System (MIS) in implementing Customer Relationship Management (CRM) to increase customer loyalty in retail companies. In the midst of increasingly fierce business competition, the implementation of CRM is considered a strategic solution to strengthen relationships with customers. This research uses the literature review method to identify and analyze various relevant literature regarding the application of CRM and its impact on customer loyalty. Evaluation of CRM effectiveness can be done by comparing whether CRM implementation is effective in increasing customer loyalty compared to conditions without CRM. This comparison can be seen from the results of the literature review that has been collected. The results of the analysis show that the use of CRM can increase customer satisfaction and loyalty through better data management, more personalized interactions, and effective loyalty programs in its application. However, challenges in CRM implementation, such as system integration, employee training needs, and limited technology resources, are also identified. This article provides recommendations for the optimization of marketing management information systems through increased use of technology and continuous training for employees. With a deeper understanding of the effectiveness of CRM, it is expected that retail companies can improve their marketing strategies and create a sustainable competitive advantage.